2013
DOI: 10.1021/jp406567d
|View full text |Cite
|
Sign up to set email alerts
|

Study of CO and Hydrogen Interactions on Carbon-Supported Pt Nanoparticles by Quadrupole Mass Spectrometry and Operando Diffuse Reflectance FTIR Spectroscopy

Abstract: CO adsorption on carbon-supported Pt nanoparticles under operando conditions was studied by quadrupole mass spectrometry and diffuse reflectance infrared fourier transform spectroscopy (DRIFTS). The Pt catalyst was also studied by high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD). It was shown by HRTEM and XPS that Pt nanoparticles can be fully reduced by H2 at room temperature instead of by conventional high-temperature treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…It seems plausible that the existence of Pt surface sites at the interface between the support and the Pt particles (close contact between silica and platinum as shown in Fig. S5) are accessible to CO. A similar particle-support interface effect on CO adsorption has been reported in other literature [57]. Based on these results, it could be suggested that silica coating would influence not only the amount but also the nature of exposed Pt particles.…”
Section: Structure-performance Relationshipsupporting
confidence: 87%
“…It seems plausible that the existence of Pt surface sites at the interface between the support and the Pt particles (close contact between silica and platinum as shown in Fig. S5) are accessible to CO. A similar particle-support interface effect on CO adsorption has been reported in other literature [57]. Based on these results, it could be suggested that silica coating would influence not only the amount but also the nature of exposed Pt particles.…”
Section: Structure-performance Relationshipsupporting
confidence: 87%
“…planes, edges, corners) that can have different reactivity [52]. The studies of CO adsorption on Pt showed the strongest bonding on low-coordination atoms located on the edges of NP [32]. Indeed, strong adsorption of electron-rich unsaturated carbon-carbon bonds on low-coordination edge atoms led to a decrease in selectivity toward the olefin product [53].…”
Section: Catalytic Resultsmentioning
confidence: 99%
“…bridged/triple mode of CO adsorption on Pt planes and edges), while Pt-Zn/HPS sample shows only a small shoulder at 1980 cm À1 after CO evacuation ascribed to bridged CO species on Pt planes [32,36,37]. Such deviations in the spectra bring to a conclusion about different surface structures of metal NPs in two catalysts, i.e., the NP surface in Pt/HPS is composed of atoms ensembles that are absent on the NP surface of Pt-Zn/HPS.…”
Section: Catalyst Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…The band located at 2178 cm −1 , has been previously attributed to CO adsorbed on weak Lewis acid sites of the Al 2 O 3 support [35][36][37][38]. The band at 2038 cm −1 appears at wavenumbers corresponding to CO linearly adsorbed on Pt step sites [39][40][41][42][43][44][45][46], whereas the weak band at 1787 cm −1 has been assigned to CO adsorbed in bridge form on Pt step sites [25,27,28,31]. However, the low frequency of the latter band could be also related to 3-fold bridged CO species [42,45].…”
Section: Variation Of the Population Of Pt Terrace Sites With Pt Crysmentioning
confidence: 99%